Inflammatory Bowel Disease in Hispanics: The University of Puerto Rico IBD Registry - Esther A. Torres; Abdiel Cruz; Mariola Monagas; Marina Bernal; Yadira Correa; Rafael Cordero; Víctor L. Carlo (Hindawi Limited, 2012)
A registry of patients with inflammatory bowel diseases, ulcerative colitis (UC) and Crohn's disease (CD), was created at the University of Puerto Rico in 1995. Subjects with a documented diagnosis of IBD by clinical, radiologic, endoscopic, and/or pathologic criteria were recruited from the IBD clinics, support groups, and community practices, and demographic and medical data was collected. All entries from 1995 to 2009 were analyzed for demographics, family history, disease extent, extraintestinal manifestations, surgery, and smoking history. Results were described using summary statistics. 635 Hispanics living in Puerto Rico, 299 with UC and 336 with CD, were included. Mean ages were 40.3 for UC and 30.9 for CD. Over half (56%) of UC and 41% of CD were females. Family history was present in 19.3% of UC and 17.5% of CD. Surgery for IBD had been performed in 31.9% of UC and 51.2% of the CD patients. Over one-fourth of the patients reported extraintestinal manifestations, most frequently arthropathies. Our findings contribute to the limited epidemiologic and clinical data on Hispanics with IBD.